Numerical analysis of the abnormal water level rise phenomenon on the west coast of Ca Mau Peninsula, Vietnam - Thuy, Nguyen Ba; Tien, Pham Van; Cuong, Nguyen Kim; Ngoc, Pham Khanh; Dang, Vu Hai; Quyet, Le Dinh; Kim, Sooyoul; Wettre, Cecilie; Hole, Lars Robert (Frontiers in Built Environment, 2025)
The abnormal water level rise on the west coast of Ca Mau Peninsula, Vietnam, has dramatically increased as extreme events have intensified in recent decades. To forecast it, it is necessary to understand the mechanism. However, its mechanism has yet to be studied. Based on the numerical simulation results, this study discusses abnormal water level change in a case study during the afternoon of August 2–3, 2019, and 11 July 2022. A coupled model of surge wave and tide (called SuWAT) was applied to simulate the tide, surge, and wind wave. SuWAT’s simulations were validated with the observational data of total water level and significant wave height, and the model could sufficiently reproduce the tidal, wind-induced surge and wave. The findings indicate that the unusual water level fluctuations along the western coast of the Ca Mau Peninsula resulted from a combination of high astronomical tides, storm surges, and waves. Notably, long-period swells substantially contributed to the overall water level, with peak measurements reaching 0.52 m on 3 August 2019, and 0.53 m on 11 July 2022. These surges and swell effects are mainly attributed to the study area’s prolonged and intense southwest monsoon.